The Relationship of Feminine Gender Roles to Fear of Success in Working Women - Alicia Kusuma Wardani; Ratriana Y. E. Kusumiati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to examine the relationship between feminine gender roles and fear of success in working women aged twenty to forty years. Various theories suggest that successful women tend to fear losing their femininity, making this empirical investigation essential. A quantitative correlational research method with probability sampling was employed. The participants were 150 working women recruited via online questionnaires. The instruments used were the Bem Sex Role Inventory (BSRI) to measure feminine gender role and the Fear of Success Scale (FOSS) by Zuckerman and Allison to measure fear of success. Hypothesis testing revealed a correlation coefficient of -0.210 with a significance value of 0.010, leading to the rejection of the alternative hypothesis and acceptance of the null hypothesis. In conclusion, there is no significant relationship between feminine gender roles and fear of success in working women. These findings indicate that the manifestation and factors of feminine gender role can occur and be influenced by factors other than fear of success, such as educational experiences, cultural context, family support, work-family conflict management, and individual psychological resources including self-compassion and resilience. Keywords: feminine gender role, fear of success, working women